THE USE OF LOGOS, PATHOS AND ETHOS IN STUDENT REASONING: A GENDER-BASED ANALYSIS USING THE ENNIS-WEIR CRITICAL THINKING ESSAY TEST - Shaari, Farah Fatinah Enche (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This qualitative study investigates gender-based differences through the use if Aristotle’s rhetorical appeals (Logos, Pathos and Ethos) in students’ critical thinking performance specifically, reasoning. Using the Ennis-Weir Critical Thinking Essay Test as the instrument and Aristotle’s rhetorical framework as the conceptual lens, the study aimed to identify the most and least preferred appeal employed by male and female respondents when constructing argumentative responses. This study involved ten first year second-semester diploma students (five male and five female) from a local public university. Their written responses were analysed to identify instances of reasoning and classify them according to Aristotle’s appeals. The findings indicated that logos, or logical reasoning, was the most frequently used appeal by both genders which highlighted a shared emphasis on rational and structured argumentation. However, gender differences were evident in the use of pathos. Female respondents employed the emotional appeal specifically to invoke empathy, safety concerns and social well-being. Whereas, male respondents used pathos less frequently. This suggests a tendency among female respondents to integrate emotional and relational elements into their reasoning. Ethos or ethical appeal, was the least preferred by both genders, likely due to the limited opportunity within the task to establish personal credibility seen in the nature of the question posed. The results suggest that while logical reasoning is universally prioritised in structured academic contexts, female respondents are more inclined to employ affective appeals, producing a more nuanced and multi-dimensional rhetorical approach.